The effect of maximum speed training at different distances on the anaerobic capacity and scoring accuracy of soccer players - Abboud, Naseer Mizher; Ne’ma Kadhim, Evan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this study was twofold: firstly, to prepare exercises aimed at enhancing maximum speed at varying distances for soccer players. Secondly, to investigate the impact of maximum speed training at different distances on the anaerobic capacity and scoring accuracy of soccer players. The researchers employed an experimental approach with two equivalent groups in both the pre-test and post-test phases for both the experimental and control samples. The research community comprised players from the Football Development Club, totaling 30 players. A random selection process was utilized to choose a sample consisting of 20 players. This sample was then divided into two groups: the experimental group, consisting of 10 players, and the control group, also consisting of 10 players. For statistical analysis, researchers used the SPSS program. There were significant differences between the results of the post-tests of the research variables of the control and experimental groups and in favor of the experimental group. The positive results attained by the players of the experimental group in anaerobic ability stemmed from the exercises they employed, which facilitated the enhancement of this ability.